Buddhist wisdom as a path to a new economic enlightenment. Issue 8 (2nd September 2014) - Sirodom, Kulpatra; R. Loza Adaui, Cristian; Habisch, André; Lenssen, Gilbert; Roosevelt Malloch, Theodore; Stirling, Kate
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to argue that mainstream economic theory leads to a diminishment of human happiness and well-being. Alternatively, Buddhist wisdom, applied to economic decision making, offers the opportunity for a well-lived life of purpose and meaning. Design/methodology/approach – The paper begins with an examination of the foundational elements of Buddhism and economics, then contrasts the paths (or models) constructed from these bases and the associated implications for happiness and well-being. Findings – The assumptions of Buddhism and economics regarding incessant wants, method of analytical inquiry, assignation of primary agency, and promotion of individual freedom, all bear striking similarities. Yet, despite these commonalities, the paths they undertake could not be more different. Specifically, their views and beliefs regarding consumption, work, and self-interest lead to radically different implications for how to live a well-lived life and how to organize economic society. Research limitations/implications – Business leaders should develop alternative business models that incorporate a broader range of values and ideals than those associated with traditional economic modeling. Explicit inclusion of a firm's social responsibilities can be implemented via social accounting procedures and its mission statement. Responding to consumer demand for goods that are produced fairly, humanely, and sustainably will allow firms to do well by doing good. Originality/value – Significant and detrimental consequences arise from the adherence to the mainstream economic model. Buddhist wisdom, on the other hand, provides a path that offers an alternative vision of economic society, one that would likely lead to greater human fulfillment.